Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Penghindaran Pajak - Rista Amalia; Sri Purwaningsih (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The objective of this study was to evaluate the influence of profitability, liquidity, and company size on the propensity for tax avoidance among mining companies listed on the Indonesia Stock Exchange between 2019 and 2021. The present study focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the same year. A total of 60 samples were selected from 23 companies that met the criteria established for this study. The sample was selected through the use of purposive sampling. The analytical approach employed is a multiple linear regression model with independent and dependent variables, which is processed using the Eviews 12 program. The findings of the research indicate that there is a negative correlation between profitability and tax avoidance, as well as between liquidity and tax avoidance. However, the results suggest that company size does not exert a significant influence on tax avoidance.